Unraveling the Notion of "Fair Carbon": Key Challenges for Standards Development. (June 2015) - Howard, Rebecca Joy; Tallontire, Anne; Stringer, Lindsay; Marchant, Rob
Highlights: Critical analysis of standard setting processes in the voluntary carbon market. Focus on access and benefit-sharing as key components in notions of fair carbon. Considers practical constraints shaping fairness outcomes within carbon projects. Outlines role of standard-setting-organizations in brokering access or exclusion. Summary: Standards organizations and NGOs have begun to refer to "fair carbon" projects, and "fairly traded" carbon credits. "Fairness" is a fuzzy notion, subject to multiple and competing interpretations. This paper draws on a framing used by standards organizations, which encompasses issues of access and benefits, to critically examine challenges and opportunities for achieving desired "fair" outcomes as discussed in the literature. Arising knowledge gaps are presented as a research agenda that explores what "fair carbon" means to multiple stakeholders; illuminates governance processes through which "fairness" is being standardized; and examines its implications within certified carbon projects.